(untitled) (International journal of artificial intelligence, 2026)
This article examines the sociolinguistic characteristics of educational folk proverbs in English and Uzbek through a comparative and contextual approach. The study explores how proverbs related to upbringing and moral instruction reflect social norms, cultural values, and collective worldviews in both linguistic communities. Particular attention is paid to the social functions of proverbs in transmitting ethical principles, reinforcing behavioral standards, and shaping interpersonal relations across generations. The research analyzes proverbs within their cultural, historical, and social contexts, highlighting similarities and differences in the representation of education, morality, and social responsibility. The findings reveal that while English proverbs tend to emphasize individual responsibility and practical wisdom, Uzbek proverbs place greater focus on collective harmony, respect for elders, and moral upbringing. The article aims to identify the stable sociolinguistic features of educational proverbs and to demonstrate their role as a significant linguistic and cultural resource in understanding societal values.